Mitigating environmental pollution from tofu industry wastewater: Case of Suyanto Tofu Factory, Mojokerto - Zalfain, Muhammad; Noerhayati, Eko; Rahmawati, Anita (Applied Environmental Science, 2024)
Background: This research investigates the impact of tofu industry wastewater on the aquatic environment at the Suyanto Tofu Factory, Mojokerto. The tofu industry produces liquid waste that contains high pH, Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD), and Chemical Oxygen Demand (COD), so it has the potential to pollute local rivers. Although the Suyanto Tofu Factory has wastewater treatment facilities, these facilities are currently not functioning, indicating an urgent need to design a new wastewater treatment plant. In this context, the research aims to determine the volume of wastewater produced, analyze BOD, COD, TSS and pH levels in wastewater, and design sustainable wastewater treatment facilities for the tofu industry. Methods: The method used is planning the design Constructed Wetland system with water hyacinth plants . This method is expected to minimize the environmental impact of tofu wastewater, protect the surrounding aquatic ecosystem, and comply with environmental regulations. Findings: This research found a wastewater treatment plant model using a pond system Sanita (Constructed Wetland ) which can reduce tofu waste effectively and sustainably is very important to maintain water quality and river ecosystems around the Suyanto Tofu Factory. Conclusion: The liquid waste at the Suyanto tofu factory has high levels of acidity and organic pollutants, with a pH of 3.91, TSS of 1050 mg/L, BOD of 2063 mg/L, and COD of 5135 mg/L. The factory uses a wastewater management design involving Sanita Pond processing with Eichhornia crassipes plants, effectively reducing the organic content in the waste. Novelty/Originality of this Study: By proposing a Constructed Wetland system for tofu industry wastewater treatment, this research introduces an innovative, sustainable solution tailored to local conditions, potentially revolutionizing waste management practices in small-scale food industries.